Travel across more time zones results in worse perceived fatigue and sleep in national-team footballers - Clements, E.; Ehrmann, F.; Clark, A.; Jones, M.; McCall, A.; Duffield, R. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study investigated the association between (1) time zone difference and (2) travel direction (east vs west) with posttravel changes in perceptual responses of national-team footballers.